2022
DOI: 10.1109/lra.2022.3193485
|View full text |Cite
|
Sign up to set email alerts
|

A New Power Law Linking the Speed to the Geometry of Tool-Tip Orientation in Teleoperation of a Robot-Assisted Surgical System

Abstract: Fine manipulation is important in dexterous tasks executed via teleoperation, including in robot-assisted surgery. Discovering fundamental laws of human movement can benefit the design and control of teleoperated systems, and the training of their users. These laws are formulated as motor invariants, such as the well-studied speed-curvature power law. However, while the majority of these laws characterize translational movements, fine manipulation requires controlling the orientation of objects as well. This s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Taken together, these results imply that the orientation of the hand is under kinematic control, yet the control is imperfect. The optimization of kinematics is also supported by our additional study that found a new power law that links the angular speed of a remote controlled tool that rotates around its center of mass with the local curvature of its orientation path [ 50 ]. Such optimization was observed in translational hand movements and is known as the speed-curvature power law [ 51 ], which was also observed in manipulation of remote controlled rigid bodies [ 52 ].…”
Section: Discussionmentioning
confidence: 91%
“…Taken together, these results imply that the orientation of the hand is under kinematic control, yet the control is imperfect. The optimization of kinematics is also supported by our additional study that found a new power law that links the angular speed of a remote controlled tool that rotates around its center of mass with the local curvature of its orientation path [ 50 ]. Such optimization was observed in translational hand movements and is known as the speed-curvature power law [ 51 ], which was also observed in manipulation of remote controlled rigid bodies [ 52 ].…”
Section: Discussionmentioning
confidence: 91%